2011
DOI: 10.1016/j.jaci.2010.12.532
|View full text |Cite
|
Sign up to set email alerts
|

Most Nocturnal Asthma Symptoms Occur Outside of Exacerbations and Associate with Morbidity

Abstract: Background-Although nocturnal awakenings help categorize asthma severity and control, their clinical significance has not been thoroughly studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
1
4
0
1
Order By: Relevance
“…Together these findings highlight sleep disruptions in young children with asthma, most notable in children with poorly controlled asthma, but also when asthma is well-controlled, similar to previous findings in older children and adolescents (e.g. Daniel et al, 2012; Horner et al, 2011; Meltzer et al, 2014).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Together these findings highlight sleep disruptions in young children with asthma, most notable in children with poorly controlled asthma, but also when asthma is well-controlled, similar to previous findings in older children and adolescents (e.g. Daniel et al, 2012; Horner et al, 2011; Meltzer et al, 2014).…”
Section: Discussionsupporting
confidence: 85%
“…Sleep problems are common in youth with asthma (Daniel et al, 2012; Meltzer et al, 2014), including prolonged sleep onset latency, frequent night wakings, and daytime sleepiness, even when asthma symptoms are well controlled (Chugh et al, 2006; Horner et al 2011; Sadeh et al, 1998; Stores et al, 1998; Yuksel et al, 2007). Yet only one study has examined sleep patterns in young children, with no significant differences found between young children with and without asthma (Tirosh et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…It might be argued that criteria for well‐controlled asthma in children may differ from those in adults. In children, in particular limitation of activities and nocturnal symptoms may impact the quality of life of the children and their caregivers . Based on GINA criteria, the diagnostic performances of the ACT or ACQ in assessing levels of asthma control have been evaluated in several studies.…”
Section: Gold Standard Of Asthma Controlmentioning
confidence: 99%
“…Specifically, night awaking due to asthma‐like symptoms was predictive of this outcome. Previous studies have found increased incidence of sleep difficulties in preschoolers with wheezing, particularly those with uncontrolled disease, suggesting that this characteristic is a marker of a more severe phenotype . Additionally, sleep deprivation may lead to an increase of proinflammatory cytokines, which could exacerbate inflammatory conditions such as asthma .…”
Section: Discussionmentioning
confidence: 99%